Geographic Distribution of Mating Type Alleles of Cryptococcus neoformans in Four Areas of the United States - Zhun Yan; Xiaogang Li; Jianping Xu (2002)
ABSTRACT To better understand the epidemiology and population structure of Cryptococcus neoformans , we determined mating types for 358 C. neoformans strains isolated through the active surveillance program from 1992 to 1994 in four geographic areas in the United States: San Francisco, California; Georgia; Texas; and Alabama. Two assays were used to determine mating types: (i) crossing with standard laboratory tester strains JEC20 and JEC21 on V8 agar medium; and (ii) PCR with the mating type α allele-specific primer of the STE12 gene and with serotype (A and D)- and mating type (a and α)-specific primers of the STE20 gene. Using these two methods, we found that this sample consisted of the following: (i) 324 serotype A, mating type ( MAT ) α (Aα) strains; (ii) 12 serotype D, α (Dα) strains; (iii) 14 serotype AD strains with mating type alleles Aa and Dα (AaDα); (iv) 2 serotype AD strains with mating type alleles Aα and Da (AαDa); (v) 3 serotype B, α (Bα) strains; and (vi) 3 serotype AD strains but with only one mating type allele. No strain with MAT a was found within serotype A, B, or D in this collection. Interestingly, 14 of the 19 serotype AD strains contained the Aa allele at the STE20 locus; 13 of these 14 were from San Francisco. Our results suggest that the environment in San Francisco might contain Aa strains capable of mating with Dα strains. In addition, our result demonstrate that the sample from San Francisco had a significantly higher proportion of self-fertile strains than those from the other three areas.